Random Drawing Strategies in Procedural Text Learning - Trian Pamungkas; Risma Khairun Nisya; Pipik Asteka; Ima Siti Rahmawati (Journal of English Language Learning, 2025)
This study aims to explore and describe the application of the syntax of random drawing strategies in learning procedural texts at the higher education level. The image randomization strategy is a visual-based method that requires students to arrange a sequence of images that have been randomized into a series of logically sequenced procedures, then convert them into the form of a procedural text. This study uses a qualitative descriptive approach, with data collection techniques through the watch-record method. This technique is applied by directly observing the learning process and recording student interactions, behaviors, and work results during the activity. The subject in this study is a second-semester student from the Indonesian Language and Literature Education Study Program at Majalengka University. Data was collected through class observation and documentation in the form of student writing. The findings of the study show that the randomized drawing strategy contributes positively to improving students' understanding of the structure of the procedural text, practicing the skills of systematically drafting steps, and encouraging active participation in the learning process. In addition, this strategy is considered interesting and helps students in developing logical and structured thinking skills more effectively. Keywords: random images, procedure text, qualitative methods, watch-note